Organic Chemistry from Retrosynthesis to Asymmetric Synthesis - Šunjić, Vitomir; Petrović Peroković, Vesna (Springer International Publishing : Imprint: Springer, 2016)
This book connects a retrosynthetic or disconnection approach with synthetic methods in the preparation of target molecules from simple, achiral ones to complex, chiral structures in the optically pure form. Retrosynthetic considerations and asymmetric syntheses are presented as closely related topics, often in the same chapter, underlining the importance of retrosynthetic consideration of target molecules neglecting stereochemistry and equipping readers to overcome the difficulties they may encounter in the planning and experimental implementation of asymmetric syntheses. This approach prepares students in advanced organic chemistry courses, and in particular young scientists working at academic and industrial laboratories, for independently solving synthetic problems and creating proposals for the synthesis of complex structures.